Bronchiolitis obliterans syndrome and survival following lung transplantation for patients with sarcoidosis - Wille, K.M.; Gaggar, A.; Hajari, et al., A.S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Background: End-stage sarcoidosis is characterized by severe pulmonary fibrosis and is often poorly responsive to medical therapy. Lung transplantation, therefore, may be the only treatment option. Currently, there are few studies evaluating long-term outcomes following transplantation for these patients. Our aim was to evaluate post-transplant morbidity and survival of patients with sarcoid compared to recipients transplanted for idiopathic pulmonary fibrosis (IPF). Methods: We retrospectively examined 300 lung transplant recipients using a dedicated database. Over a 10-year period, 15 (5.0%) patients with sarcoidosis and 48 (16%) patients with IPF were identified. Primary outcome measures included rate and time to onset of bronchiolitis obliterans syndrome (BOS) and survival. Results: Recipients in the sarcoid group were younger and predominantly female compared to recipients in the IPF group. Five of 15 (33%) sarcoid patients developed BOS versus 15 of 48 (31%) IPF patients (p=1.0). There was no significant difference in the time to BOS onset. Median survival was 1,365 days for the sarcoid group and 1,593 days for the IPF group (Hazard Ratio 0.94 by Kaplan-Meier analysis; [95% CI] 0.33-2.67; p = 0.90). Conclusions: We observe similar long term outcomes following lung transplantation for sarcoid and IPF recipients. Transplantation remains a treatment option for end-stage sarcoidosis, as BOS and survival rates are comparable to IPF.